Saline effects on forage growth and quality - Oliveira M.M.; Carmona M.A.; Santos M.J. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Birdsfoot trefoil (Lotus corniculatus L.) and tall fescue (Festuca arundinacea Schreb.) plants were grown hydroponically in pots (NFT system), with four NaCl levels: 0, 44, 87 and 174 mM (corresponding to 1, 4, 8 and 16 dS/m). Plants shoot dry weight, amino acids, proline and mineral content were analysed after 35, 78, 121 and 148 days of saline treatment. In the last sampling, dry weight was reduced in 44% and 77%, with respect to control, in birdsfoot trefoil and tall fescue, respectively, with higher salinity. At the first harvest, dry matter formation was correlated with K+ (r=0.96) in the former and with Ca2+ (r=*0.91) in the second species. The chloride content in dry matter increases with time of exposure and salinity level in both species, with a higher rate accumulation in birdsfoot trefoil. In tall fescue proline and sucrose contents were twice as high and well related with sodium (r=0.92) and chloride (r=0.98), respectively.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)